2016
DOI: 10.3389/fnsys.2016.00011
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli Reduce the Dimensionality of Cortical Activity

Abstract: The activity of ensembles of simultaneously recorded neurons can be represented as a set of points in the space of firing rates. Even though the dimension of this space is equal to the ensemble size, neural activity can be effectively localized on smaller subspaces. The dimensionality of the neural space is an important determinant of the computational tasks supported by the neural activity. Here, we investigate the dimensionality of neural ensembles from the sensory cortex of alert rats during periods of ongo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
169
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(183 citation statements)
references
References 84 publications
(227 reference statements)
9
169
0
Order By: Relevance
“…By contrast, principal components analysis (PCA), a standard dimensionality reduction method, applied to spike counts measures dimensionality of the raw covariability. Recently, Mazzucato et al used PCA to examine the dimensionality of 3 to 9 neurons recorded simultaneously in rat gustatory cortex [19]. Despite the difference in methods used to compute dimensionality, they also found that dimensionality increases with neuron and trial count in in vivo recordings and spiking network models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, principal components analysis (PCA), a standard dimensionality reduction method, applied to spike counts measures dimensionality of the raw covariability. Recently, Mazzucato et al used PCA to examine the dimensionality of 3 to 9 neurons recorded simultaneously in rat gustatory cortex [19]. Despite the difference in methods used to compute dimensionality, they also found that dimensionality increases with neuron and trial count in in vivo recordings and spiking network models.…”
Section: Discussionmentioning
confidence: 99%
“…Our study could be extended to scaling trends in evoked activity, in which visual stimuli are presented during the V1 recordings and non-zero inputs are used in the spiking network models. Previous studies have found that shared variance tends to decrease after stimulus presentation [20, 35, 3840] and that the scaling properties of PCA dimensionality change after stimulus presentation [19]. However, under certain conditions, the population activity patterns expressed in spontaneous activity can resemble those expressed in evoked activity [9, 41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a model features balanced excitation/inhibition and a clustered architecture and generates an attractor landscape that spontaneous activity explores (Figure 1e). The model built to explain spontaneous activity could reproduce fundamental features of stimulus-evoked activity [27,28], indicating that the elusive relationship between spontaneous and evoked cortical activity [33] is grounded in the dynamics internally generated by a network with clustered architecture [34]. …”
Section: Introductionmentioning
confidence: 99%